Accident prevention practices at high-rise building construction sites in Klang, Malaysia / Nur Farhana Mustafa Kamal and Wan Faida Wan Mohd Azmi - Mustafa Kamal, Nur Farhana; Wan Mohd Azmi, Wan Faida (2023)
A construction site is a place of work where there are numerous dangerous activities and accidents. Every year, many incidents occur at building construction sites, particularly high-rise building construction sites. Many unpredictable hazards and accidents lead to thousands of people being hurt or killed each year. The growth of high-rise construction projects has resulted in an increase in the number of fatalities and accidents. The main objectives of this study are to identify the causes of accidents at high-rise building construction sites and to determine the prevention practices for them. A quantitative method was employed in this research.. Data were collected from among professional workers via an online survey in the form of a close-ended questionnaire and randomly distributed to companies in Selangor for the workers to fill in. The sample size of 335 companies was determined using Krejcie and Morgan Table, based on 2637 contractor companies registered in Klang, Selangor. This survey received a 20% response rate equivalent to 66 respondents from 335 questionnaires distributed. There are many causes of accidents at high-rise building construction sites. Fall from height of the building had been ranked as the leading cause, followed by electric shock and being struck by falling objects. As for prevention of high-rise building accidents, proper housekeeping received the support of many respondents to be one of the best prevention practices to avoid accidents, followed by training skills and use of personal protective equipment (PPE). There are many measures that can be taken to prevent accidents at high-rise building construction sites, but the most selected prevention measure is doing proper housekeeping. It is believed that the accident cases can be avoided if all the workers complied with the rules.